Compact Tri-Band Microstrip Patch Antenna Using Complementary Split Ring Resonator Structure - N. Rajesh Kumar; P. D. Sathya; S. K. A. Rahim; M. Z. M. Nor; Akram Alomainy; Akaa Agbaeze Eteng, (Applied Computational Electromagnetics Society Journal (ACES), 2021)
In this letter, a compact complementary split ring based tri-band antenna is proposed. The proposed antenna resonates at 1.9 GHz (1.70-1.91 GHz), 2.45 GHz (2.23-2.52 GHz) and 3.2 GHz (2.9-3.25 GHz); the input match values are 24.56 dB, 27.21 dB and 22.46 dB, respectively. The antenna’s realised peak gain is 4.15 dBm at 1.9 GHz, 4.25 dBm at 2.4 GHz and 4.74 dBm at 3.2 GHz, with approximately 42% of reduction in antenna size. The results demonstrate that the proposed metamaterial antenna is tunable, electrically small and highly efficient, which makes it a suitable candidate for RF energy harvesting. The antenna is numerically and experimentally analysed and validated with very good comparison between the simulated and measured results.